COMBINATION OF RADIATION THERAPY AND FIROCOXIB FOR THE TREATMENT OF CANINE NASAL CARCINOMA. Issue 3 (21st February 2015) - Cancedda, Simona; Sabattini, Silvia; Bettini, Giuliano; Leone, Vito F.; Laganga, Paola; Rossi, Federica; Terragni, Rossella; Gnudi, Giacomo; Vignoli, Massimo
<x xml:space="preserve">Abstract</x> Carcinomas represent two‐thirds of canine nasosinal neoplasms. Although radiation therapy (RT) is the standard of care, the incidence of local recurrence following treatment is high. Cyclooxygenase‐isoform‐2 (COX‐2) is expressed in 71–95% of canine nasal carcinomas and has been implicated in tumor growth and angiogenesis. Accordingly, COX‐2 inhibition seems rational to improve outcome. Dogs with histologically confirmed, previously untreated nasal carcinomas were randomized to receive the combination of a selective COX‐2 inhibitor (firocoxib) and palliative RT (Group 1) or RT and placebo (Group 2). Patients were regularly monitored with blood tests, urinalysis, and computed tomography. Pet owners were asked to complete monthly a quality‐of‐life questionnaire. Twenty‐four dogs were prospectively enrolled. According to Adams modified system, there were five stage 1, five stage 2, three stage 3, and 11 stage 4 tumors. Two dogs had metastases to regional lymph nodes. Median progression‐free interval and overall survival were 228 and 335 days in Group 1 (n = 12) and 234 and 244 days in Group 2 (n = 12). These differences were not statistically significant. The involvement of regional lymph nodes was significantly associated with progression‐free interval and overall survival (P = 0.004). Quality of life was significantly improved in Group 1 (P = 0.008). In particular, a significant difference was observed for activity and appetite. Although not providing a significant enhancement of progression‐free interval and overall survival, firocoxib in combination with RT is safe and improved life quality in dogs with nasal carcinomas.